RISK MANAGEMENT ANALYSIS ON MUSHARAKAH PROFIT-SHARING FINANCING AT BANK BPRS MENTARI PASAMAN SAIYO WEST PASAMAN - Orizal, Orizal; Yossieroawati, Yossieroawati; Rahmad, Fawza; Leli, Maisarah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
BackgroundThe main problem in this study is related to the analysis of low risk management in Musharakah profit-sharing financing at Bank BPRS Mentari Pasaman Saiyo West Pasaman. Furthermore, the problem is divided into several formulations, namely 1.) What is the form of the implementation of the risk sharing of musharakah profits in BPRS-MPS Simpang Empat, 2.) and description of the form of BPRS-MPS Simpang Empat strategy to reduce risks in musharakah financing.Purpose This study is to find out the form of implementation of Musharakah Profit Sharing Risk Reduction in BPRS-MPS Simpang Empat and the form of BPRS-MPS Simpang Empat strategy to reduce risks in Musharakah financing. This study uses the Field Research methodMethod. The type of approach is qualitative, The source of this research data is Bank BPRS Mentari Pasaman Saiyo and Musharakah financing profit sharing customers at Bank BPRS Mentari Pasaman Siayo. This primary data was obtained through interviews with informants, namely with the Bank and profit-sharing financing customers of Bank Musharakah Bank BPRS Mentari Pasaman Siayo Pasaman Barat.Results. Research shows that in the implementation of the Risk Sharing of Musyarakah at BPRS-MPS Simpang Empat that the profit sharing that is carried out is distributed in accordance with the agreement between the two parties and is divided according to the portion of capital at the beginning of the partnership. The determination of profit sharing at BPRS Mentari Saiyo West Pasaman is determined by determining the profit sharing ratio first in the form of a percentage. As well as the Strategy of BPRS-MPS Simpang Empat to Reduce Risks in Musharakah Financing Strategies to Minimize Risks in Musharakah Financing at BPRS Mentari Saiyo Pasaman Barat,Conclusion. Pihak BPRS Mentari Saiyo Pasaman Barat dalam meminimalisir potensi timbulnya risiko pada pembiayaan musyarakah. Bentuk mitigasi tersebut adalah dengan melakukan analisis terhadap kelayakan nasabah menerima pembiayaan dengan menggunakan prinsip 5C (character, capacity, capital, collateral dan condition of economy).